Performance of Raitha Samparka Kendras in Davangere District of Karnataka - Patil, Ramappa; Nanjappa, D; Raghuraja, J; Beerannavar, Basavaraj (Journal of Agricultural Extension Management, 2018)
The study was conducted to assess the performance of Raitha Samparka Kendras (RSKs) of Davanagere District of Karnataka. Extension personnel and farmers constitute the sample for the study. The results regarding overall performance of RSKs reveal that 37.78 per cent of extension personnel indicated that RSKs had medium level of performance followed by equal (31.11%) percentage of extension personnel who indicated that RSKs had high and low level of performance. Less than half (40.00%) of the extension personnel indicated that there was a medium level of performance of RSKs with respect to infrastructure and other physical facilities, whereas 31.12 per cent and 28.88 per cent of extension personnel indicated low and high level of performance of RSKs. About 44.45 per cent of extension personnel indicated that RSKs had medium level of performance with regard to supply of critical inputs and customized services to farmers. A majority (86.66%) of extension personnel indicated that RSKs had medium level of performance on the planning for agricultural extension activities. With regard to formation of farmers groups 46.67 per cent of RSKs had medium level of performance. About 60.00 per cent of extension personnel indicated that RSKs had high level of performance with respect to follow up of extension activities. Less than half (42.22%) of farmers indicated that RSKs of Davangere district had medium level of performance on overall performance on different dimensions viz., dissemination of agricultural information, planning of extension activities, input supply and custom hiring services and follow up of extension activities.